Perancangan Prosedur Berbasis Manajemen Risiko pada Sistem Manajemen Mutu ISO 9001:2015 di PT XYZ - Arif Rahman; Surya Perdana (Sosio e-Kons, 2020)
Standards that generally must be owned by companies in order to achieve a good management system are ISO 9001 international standards, these standards govern the company's quality management system. PT XYZ is a printing company, this company has obtained the ISO 9001 certification version in 2008. However, there are the latest developments where in September 2015, ISO issued the latest revised standard so that the ISO 9001: 2008 standard is no longer valid. Therefore, PT XYZ is obliged to migrate or change its standards following the latest revised standard requirements, namely ISO 9001:2015 no later than 2018. The method of risk management analysis is carried out by entering identified risks into the risk management form. Furthermore, the risk of failure and its effect is determined by two factors, namely: the magnitude of the impact if a failure occurs, the second is the probability and frequency of failure. After the classification is carried out, the weighting calculation is performed for all identified risks (risk assessment). Identified risks and their weights are entered into the risk register according to priority, where the risk with the highest weight is placed in the top position. Based on the results of high-risk research (H), namely the production process inspection process and the final inspection QC process. For medium risks, there are 3, namely the process of making COAs, the Incoming Material Inspection process, and the process of handling complaints.